Amino Acid Substitution K470R in the Nucleoprotein Increases the Virulence of H5N1 Influenza A Virus in Mammals - Chen, Lin; Wang, Chengmin; Luo, Jing; Li, Meng; Liu, Huimin; Zhao, Na; Huang, Jingjing; Zhu, Xili; Ma, Guoyao; Yuan, Guohui; He, Hongxuan (Frontiers in Microbiology, 2017)
H5N1 is a highly pathogenic influenza A virus (IAV) and poses a major threat to the public health. The nucleoprotein (NP) has a multiple functions during the viral life cycle, however, the precise role of NP mutants in viral replication and pathogenicity is not completely understood. Here, we attempted to identify five residues in NP that may contribute to viral replication or pathogenicity. Of these, K227R, K229R and K470R viruses were successfully rescued by reverse genetic, but the K91R and K198R viruses were not viable. A mini-genome assay demonstrated that the NP mutations K91R and K198R significantly decreased the polymerase activity. Moreover, these two mutations resulted in disrupted cellular localization in mammalian cells. Importantly, mutation at position 470 of NP significantly increased its virulence in vitro and in vivo. These findings demonstrated that the NP protein plays a major role in influenza virulence and pathogenicity, which adds to the knowledge of IAV virulence determinants and may benefit IAV surveillance.